P1373Assessment of atrial fibrillation cryoablation outcomes in patients with diabetes. (18th June 2020) - Sener, Y Z; Oksul, M; Akkaya, F; Ates, A H; Canpolat, U; Yorgun, H; Aytemir, K
Abstract: Background: Diabetes is related with both AF occurence and increased thromboembolic risk. There is scarce data about the outcomes of AF catheter ablation in patients with diabetes. Purpose: We aimed to evaluate outcomes of AF catheter ablation in patients with diabetes. Methods: All patients underwent AF cryoablation between January 2013 and January 2018 were included .   Results: A total of 493 patients were enrolled. Mean age was 59.6 ± 11.8 years and 253 (51.3 %) patients were female. Median follow up time was 28 (6-59) months. Recurrence occured in 61 (12.4%) patients. Diabetes was present in 78 (16%) cases. Mean HbA1c value of the diabetic patients was 6.79 ± 1.02 %. 50 (64.1 %) patients was under treatment with only oral antidiabetics while others were using insulin. Diabetic group was older (p < 0.001) and hypertension prevalance was significantly higher in diabetics(p < 0.001). Complication and recurrence rates were similar between the two groups (Table-1). Subgroup analysis revealed that there was not significant difference by AF recurrence between not only patients treated with OAD alone and treated with insulin but also patients with HbA1c value <7 and HbA1c value ≥7 (p = 0.064). Conclusion: Recurrence and complication rates were similar between diabetic and non-diabetic patients. Despite neuropathy is a well known manifestation of diabetes; phrenic nerve damage rate is similar in diabetic patients with non-diabetic counterparts.